Business and regional innovation culture: An overview of the conceptualization of innovation culture - Fotios Katimertzopoulos; Charis Blados; Theodore Koutroukis (Administrative Sciences, 2023)
The primary aim of this paper is to identify key similarities and differences in the conceptualization of culture across the major theories of regional socioeconomic science, including economic, business, administrative, social, cultural and political dimensions acting at the regional and local scales. The second goal is to present an overview of the knowledge base and third to cohesively examine and partially recreate the topic using the semi-systematic review method. The final objective of examining the aforementioned issues is to clarify the dynamic correlation in the structuring of business and innovation culture, as well as to identify the characteristics that contribute to the sustainable culture of business and regional innovation systems, including long-term sustainable development. The research shows that the coexistence and combination of innovative culture at the business and regional levels should be perceived as a dynamic and co-evolutionary process involving a variety of factors. Local organizations and institutes that foster entrepreneurship are among the elements that enhance the innovation culture; however, having all of the resources in isolation is insufficient for an efficient ecosystem. This study proposes the establishment of a framework that will enhance the growth of innovation, cultural evolution and regional ecosystem performance. The Institutes of Local Development and Innovation (ILDI) are a policy idea that might give effective micro-meso-level solutions for the region. These policy proposals will diagnose the regional business culture under the prism of strategy, technology, and management levels. The specific investigation attempted in this paper demonstrates that several converging fruitful paths have already been created in the relative international literature. These paths could be combined and deepened further by studying the close evolutionary interconnection between business and regional innovation culture as it emerges at a global scale in the present.
Keywords: 350; business culture; innovation culture; Institutes of Local Development and Innovation (ILDI); regional culture; regional development; regional innovation system; Stra.Tech.Man Innovation approach